b - Walker, Sally M.; Flannery, Tim F. (Tim Fridtjof), 1956- (b, 2009)
Offers a look at the history of climate change, how it will unfold over the next century, and what we can do to prevent a cataclysmic future.
Adapted from: The weather makers / Tim Flannery.
Includes bibliographical references (p. 289-297) and index.
Keywords: Climatic changes -- Juvenile literature; Climatology -- Observations -- Juvenile literature; Global warming -- Juvenile literature; Climatic changes; Climatology -- Observations; Global warming